Implementation level of best practice policies by Italian government for healthier food environments. (30th September 2020) - Zace, D; Specchia, M L; Di Pilla, A; Carini, E; Cacciatore, P; Frisicale, E; Silano, M; Ricciardi, W; Sassi, F
Abstract: Background: Government actions play a critical role in shaping healthy food environments, which can improve population's diet and decrease the burden of disease. This study aims to determine and compare the level of policy implementation for healthy food environments in Italy with reference to international benchmarks and make prioritized recommendations based on the identified implementation gaps. Methods: The Healthy Food Environment Policy Index (Food-EPI) tool from the International Network for Food and Obesity/NCDs Research, Monitoring and Action Support (INFORMAS) was adapted for the Italian context. This tool includes two components, thirteen domains and fifty good practice indicators, which were verified with experts from National Health Institute (NHI). Evidence for implementation was gathered and summarized for all fifty indicators from data sources such as governmental websites, non-government organizations publications and websites and via direct contact with government officials. After collecting all evidence, experts from the NHI verified the completeness and accuracy of it. The evidence document will be presented to stakeholders, aiming to seek consensus on the priority actions to be implemented by the Italian Government to improve food environments. Results: The evidence for policy implementation concerning Italy varied among domains and indicators. We found the highest level of evidence within three domains: Food Composition (2/2 indicators), Food Labelling (3/4 indicators) and Food Promotion (4/5 indicators). The domains with less identified evidence were Food Prices (1/4 indicators), Food Retail (0/4 indicators), Food Trade and Investment (0/2 indicators) and Platforms and Interaction (1/4 indicators). Conclusions: The evidence summarization and the upcoming stakeholders' meeting to rate the level of implementation for each indicator in Italy, have the potential to improve government commitment to shape healthier food environments. Key messages: Food environment policies, implemented by the government, play a key role in the health of the population, decreasing the burden of disease. Several food environment policies have been implemented and supported by the Italian government but there are still some priority actions to be taken towards healthier food environments.